'Enclosing Some Snapshots': James Patrick Brady, Photography, and Political Activism. Issue 3 (3rd July 2018) - Farrell Racette, Sherry
Abstract : James Brady was a mid twentieth-century Indigenous political organiser, trapper, prospector, writer, and intellectual. He was also a prolific photographer. This article considers the significance and aesthetics of Brady's photographic archive through the lens of Indigenous visual sovereignty. Brady was Métis – one of Canada's three recognised Indigenous peoples along with First Nations and Inuit. The Métis engaged in two conflicts with the Canadian state and negotiated the entry of a province into confederation. For a significant period of history, they lived outside Canadian infrastructures, whether the system of First Nations' reserves created in the post-treaty era or Euro-Canadian settlements. Particularly vulnerable to land loss and displacement, the Métis were in desperate condition when Brady first began travelling with his camera. Brady's photographs document the political rebirth of Métis people and the resilience and persistence of Métis communities in northern Alberta and Saskatchewan. They bear photographic witness to the lived experience of sovereignty rooted to place and continue to resonate with his subjects and their descendants.